The effect of axial stability exercises with dynamic contraction on the electrical activity of the rectus femoris muscles and the accuracy of shooting from a fixed position with a basketball - Khalaf, Zainab (Journal of Physical Education, 2024)
The research aimed to prepare pivotal stability exercises with moving contraction for young basketball players, and to identify the effect of pivotal stability exercises with moving contraction on the electrical activity of the rectus femoris muscles of basketball players, and to identify the effect of pivotal stability exercises with moving contraction on the accuracy of shooting skill from a fixed position with a basketball. The boundaries of the research community were represented by young basketball players at Al-Karkh Sports Club, whose total number is (14) players, who are continuing their training for the sports season (2023/2024). The research sample was deliberately selected from them using the comprehensive enumeration method at a rate of (100%) of their original community. After determining the measurement tools, (24) training units were prepared for pivotal stability exercises with moving contraction, as they were applied over a period of (8) weeks at a rate of (3) training units per week, and the experiment was conducted during the special preparation period for the sports season (2023/2024), as the experiment began by applying the pre-tests on Sunday corresponding to the date (12/3/2023), and then applying these exercises to the experimental group players for the period from Monday corresponding to the date (12/4/2024) until Wednesday corresponding to the date (1/24/2024), and completing this experiment by applying the post-tests on Thursday corresponding to the date (1/25/2024), and the results were processed using the (SPSS) system to be the conclusions and recommendations that preparing the pivotal stability exercises with the moving contraction and applying them is suitable for young basketball players, and that applying them helps improve the level of the electrical signal (EMG) by increasing the level of the peak and decreasing the area, and helps improve the level of shooting accuracy from a fixed basketball for young basketball players, and it is necessary when preparing pivotal stability exercises with the moving contraction when training shooting accuracy from a fixed basketball to adopt the principle of experimentation in that the point of influence is on the leg muscles to increase the level of neuromuscular control for the stability of muscle contraction in the two thigh muscles, and it is necessary to take into account not to exaggerate in increasing the allocated time For core stability exercises in the main part of the training unit, take into account the balance of training with the other muscles of the body